МЕҲНАТ ТАЪЛИМИ ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШДА ИНТЕРФАОЛ ЎҚИТИШ УСУЛЛАРИДАН ФОЙДАЛАНИШ УСЛУБЛАРИ - Балтабаев, Ж.О. (SCIENCE and SOCIETY, 2019)
In the article the author describes the modern methods of education used in the higher education system to develop further the independence of future teachers and the ability to cope with any pedagogical situation.